UNDERWEIGHT, STUNTING, WASTING DAN KAITANNYA TERHADAP ASUPAN MAKAN, PENGETAHUAN IBU, DAN PEMANFAATAN PELAYANAN KESEHATAN - Risky Amelia Rhamadani; reny noviasty; Ratno Adrianto (JURNAL RISET GIZI, 2020)
Background : Nutrition problems in toddlers become a public health problem when it exceeds WHO indicators in which the issue of malnutrition and undernutrition 17.8%, short toddlers 27.5% and thin toddlers 11.1%. The problem of undernutrition, short and thin toddlers are public health problem in the chronic category.Objective :  to determine the factor related to the nutritional status of toddlers in Loa Ipuh Health Centre. The design of this research is a cross-sectional study with total sample of 97 toddlers. Data collection uses anthropometric measurements, 24 hours of form food recall and questionnaires for mother's knowledge of breastfeeding complementary feeding and the utilization of health services.Method : Data analysis is using Pearson product-moment test with a significance level of 0.05. The results showed that there was a significant positive relationship between the food intake with the WAZ (P=0,000), HAZ (P=0,000) and  WHZ (P=0,021), mother's knowledge about complementary feeding with the WAZ (P=0,041), HAZ (P=0,010) and WHZ (P=0,010), utilization of health services with the WAZ (P=0,007), HAZ (P=0,009) and WHZ (P=0,006). Result : there is a significant positive relationship between intake of toddler feeding, mother's knowledge about complementary feeding and the utilization of health services with the nutritional status of toddlers WAZ, HAZ, and WHZ. Access to health services should be improved and evenly distributed throughout the health centre area.Conclusion : There is a significant positive relationship between food intake for children under five, maternal knowledge about complementary foods and health service utilization with the nutritional status